EKSISTENSI JEPANG DAN TIONGKOK DALAM GEOPOLITIK ENERGI DI ASIA TENGAH - Ayu Suhartini; Dian Permata Pratiwi; Jorshy Amanda Sudarno; Paulus Anggiat Siregar; Shybill Natalia de Queljoe; Syahrir Roni Geyasra (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2018)
Abstract In addition to its existence stretching along Silk Road between Europe and East Asia which later made it theheart of Euroasia, the Central Asia region is also a region rich in energy resources, specifically oil and naturalgas. These two factors then brought the region of Central Asia to develop into the second largest oil and gasproducing region in the world, after the Middle East. This makes the Central Asian region as an arena as well asa battle theater for energy interests between western countries, Russia, China, Japan, South Asian countries andthe Middle East. Japan and China particulary, in the past decade began to show their interest and concentrationin this region. This can be seen through the establishment of the 2004 Central Asia Plus Japan Dialogue and the2006 Official Development Assistance (ODA) by Japan. Do not want to fall behind, in 2013 through itsPresident, Xi Jinping, China building the cooperation with the Central Asia through the One Belt One Road(OBOR) initiative. The purpose of this paper is to explain how the existence of Japan and China and theirinfluence in the dynamics of geopolitical energy in the Central Asian region. To complete this paper, the authorused qualitative research methods. From this paper, it was found that the existence of Japan and China hadpositive impact on the dynamics of energy geopolitics in the Central Asia region. Keywords: Geopolitical energy, oil, natural gas, Japan, China, Central Asia. Abstrak Selain keberadaannya yang terbentang di sepanjang Silk Road antara Eropa dan Asia Timur sehinggamenjadikannya jantung dari Euroasia, Asia Tengah juga merupakan wilayah yang kaya akan sumber daya energiterutama minyak dan gas alam serta penghasil terbesar kedua di dunia setelah Timur Tengah. Hal ini membuatkawasan Asia Tengah sebagai arena sekaligus teater pertempuran kepentingan energi antara negara-negara barat,Rusia, Tiongkok, Jepang, negara-negara Asia Selatan dan Timur Tengah. Jepang dan Tiongkok secara khususdalam dekade terakhir mulai menunjukan minat dan konsentrasinya pada kawasan ini. Terbukti melaluipembentukan Central Asia Plus Japan Dialogue tahun 2004 dan Official Development Assistance (ODA) tahun2006 oleh Jepang. Tidak ingin ketinggalan pada tahun 2013 melalui Presidennya, Xi Jinping, Tiongkokmembangun kerjasama melalui inisiatif One Belt One Road (OBOR). Adapun tujun dari tulisan ini adalah untukmenjelaskan bagaimana eksistensi dan pengaruh dari keberadaan Jepang dan Tiongkok dalam dinamikageopolitik energi di kawasan Asia Tengah. Dalam menyelesaikan tulisan ini, penulis menggunakan metodepenelitian kualitatif. Dari tulisan ini didapatkan bahwa keberadaan Jepang dan Tiongkok cukup memberikanpengaruh positif bagi dinamika geopolitik energi di kawasan Asia Tengah. Kata Kunci: Geopolitik energi, minyak bumi, gas alam, Jepang, Tiongkok, Asia Tengah